A Prospective Study of Iron Status of Exclusively Breastfed Infants Weighing 1800-2499g At Birth and Correlation With Breast Milk Lactoferrin - Mehta, Manisha; Faridi, M. M. A.; Sharma, Satendra; Singh, Om; Sharma, A. K. (International Journal of Pediatrics and Child Health, 2016)
Background: Iron status of exclusively breastfed low birth weight (LBW) infants has not been evaluated sufficiently. We determined the iron status of infants weighing 1800-2499g at birth and correlated it with breast milk lactoferrin levels of their mothers. Methods: Sixty five exclusively breastfed LBW infants were recruited at 6 weeks and followed-up until 6 months of age. Iron parameters (serum iron, serum ferritin, iron binding capacity, percent transferring saturation) and breastmilk lactoferrin were measured and compared at 6 weeks and 6 months of age. Hemoglobin (Hb) was measured at 6, 10, 14, 18 weeks and 6 months of age. If at any time, Hb of the infant was <10.5g/dl then iron supplementation was started at 3mg/kg/day for a minimum of 2 months or till Hb rose to>10.5g/dl. Results: Fifty (76.9%) out of 65 infants developed anemia between 10 weeks and 6 months of age. At 6 months of age 32.2% babies showed iron deficiency (serum ferritin level <10ng/mL). There was no correlation between breast milk lactoferrin and infants’ serum iron profile either at 6 weeks or at 6 months of age. Conclusion: About 1/3rd infants developed iron deficiency state at 6 months of age. Three-fourth infants required iron supplementation by 6 months of age. There was no relationship between maternal breast milk lactoferrin with infants’ iron profile either at 6 weeks or at 6 months of age.